3D numerical analysis of exhaust flow inside a fin-and-tube evaporator used in engine waste heat recovery. (15th March 2015) - Wang, Enhua; Zhang, Hongguang; Fan, Boyuan; Ouyang, Minggao; Yang, Kai; Yang, Fuyuan; Li, Xiaojuan; Wang, Zhen
Abstract: A fin-and-tube evaporator can be used for an ORC (organic Rankine cycle) to collect waste heat of the exhaust gas of an internal combustion engine. In this paper, the thermal-hydraulic characteristics of an ORC evaporator are analyzed using a CFD method. A 3D numerical model is derived from an engineering diagram of the fin-and-tube evaporator, and the boundary conditions are specified according to the measured data obtained by the engine test. The simulation results show that the exhaust on the shell side flows primarily parallel with the fin layers. Alternating high and low temperatures appear on the middle planes of the adjacent tube rows. The shapes of the front-end and the rear-end parts connecting the main body to the exhaust pipes are important factors on the flow field. The maximum exhaust pressure decrease in the fin-and-tube evaporator is significantly less than the backpressure limit required by the engine exhaust pipe. The simulation results are verified by an engine experiment, and there exists a correlation between the numerical results and the actual heat transfer process. Highlights: Thermal-hydraulic characteristics of an ORC evaporator are analyzed. Coordination of velocity and temp. gradient is analyzed using synergy principle. Numerical results are verified by the experimental data of waste heat recovery. Convective heat transfer of the mid-planes is better than that of the center-planes. Exhaust pressure decrease is far less than the limit of backpressure of IC engine.